Wyłaniający się rynek pracy – realia i wyzwania rzeczywistości postpandemicznej - Wawrzonek, Anna (Studia Edukacyjne, 2020)
Following my research interests, I would like to reflect on professional work and focus on its new realities and challenges that the various participants of the labour market will face. As the new shape and system of forces creating the changing labour market become a challenge not only for employers, business owners, but also for employees, contractors and finally for counsellors and educators, the initial part of the study will include a short analysis of the current situation on the labour market modified by the pandemic. Next, the author will present the consequences of these changes which will be analysed from the perspective of the employer and the employee. At this point, it is worth noting that a large part of the sources on the basis of which this study was created are the internet sources, current reports, and messages which during the pandemic seem to be the most up-to-date source material.